Hypermonins A and B, two 6-norpolyprenylated acylphloroglucinols with unprecedented skeletons from Hypericum monogynum. Issue 22 (24th May 2018) - Zeng, Yan-Rong; Yi, Ping; Gu, Wei; Xiao, Chun-Xia; Huang, Lie-Jun; Tian, Dong-Song; Yan, Hui; Chen, Duo-Zhi; Yuan, Chun-Mao; Hao, Xiao-Jiang
Abstract : Hypermonins A and B, two novel 6-norpolycyclic polyprenylated acylphloroglucinols (PPAPs), were isolated from the leaves and twigs of Hypericum monogynum . Abstract : Two new 6-norpolycyclic polyprenylated acylphloroglucinols (PPAPs), hypermonins A (1 ) and B (2 ), featuring an undescribed decahydroindeno[1, 7- bc ]furan ring system, were isolated from the leaves and twigs of Hypericum monogynum . These compounds are a pair of epimers with opposite configurations at the C-5 position. Their structures, including their absolute configurations, were determined by extensive spectroscopic analysis and electronic circular dichroism (ECD) calculations. A plausible biosynthetic pathway of1 and2 was also proposed. Compound1 exhibited a significant protective effect against corticosterone-induced injury in PC12 cells.